Use of landfill leachate as a carbon source in a sulfidogenic fluidized-bed reactor for the treatment of synthetic acid mine drainage - Sahinkaya, Erkan; Dursun, Nesrin; Ozkaya, Bestamin; Kaksonen, Anna H. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
High rate sulfate reducing bioreactors can be effectively used in the treatment of acid mine drainage (AMD), The main disadvantage of sulfate reducing bioreactors is the requirement of a suitable carbon source and electron donor as the dissolved organic carbon content of AMD is usually quite low. In this study, a landfill leachate was used as a low-cost carbon source for sulfate reducing bacteria in a fluidized-bed (FBR) reactor for the treatment of synthetic AMD. Ethanol was replaced with leachate in the feed of FBR operated longer than 150 days at 35 degrees C. Although sulfate reduction rates decreased appreciably when ethanol (3.44 g sulfate/L/d) was replaced with leachate (0.90 g sulfate/L/d), leachate-fed FBR still performed well as the pH increased to neutral values, soluble metal removals were 82-99.9%, and total metal removals were 80-99.9%. In the case of leachate, electron flow to sulfate reduction decreased significantly. Higher performance may be achieved at chemical oxygen demand (COD)/sulfate ratios higher than 1.0. This study showed that leachate may be used as a low-cost soluble substrate for sulfate reducing bacteria in high rate bioreactors for AMD treatment. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Acid mine drainage; Biotreatment; Metal removal; Leachate; Carbon source; CONTAINING WASTE-WATER; SULFATE-REDUCING BACTERIA; ANAEROBIC BAFFLED REACTOR; ETHANOL; PERFORMANCE; REDUCTION; METALS; OXIDATION; Engineering; Mineralogy; Mining & Mineral Processing